2015
DOI: 10.5539/ass.v11n23p96
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Risk Taking on Relationship between Board Structure Determinants and Banks Financial Performance

Abstract: This study examines the relevance of bank board structure determinants (board independence, board size and concentrated ownership) on financial performance and level risk taking. In addition, the role of risk taking investigated as mediator variable on relationship between these variables and financial performance. This research contributes to the empirical research, Using a sample of 37 Malaysian Islamic and conventional banks over [2005][2006][2007][2008][2009][2010][2011][2012][2013][2014]. In This study, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
(58 reference statements)
3
3
1
Order By: Relevance
“…The result indicates that when firms have a majority of independent board, the less risky the firms are. This finding such consistent with (Cheng et al, 2016;Minton et al, 2012;Ni & Purda, 2012;Nodeh et al, 2015). However, there result contradict from previous literatures with McNulty et al (2012) and Shirouyehzad, Hosseinzadeh Lotfi, and Dabestani (2014) where higher proportion of non-executive directors are not initiate to have any major effect on corporate risk.…”
Section: Correlation Analysissupporting
confidence: 86%
See 3 more Smart Citations
“…The result indicates that when firms have a majority of independent board, the less risky the firms are. This finding such consistent with (Cheng et al, 2016;Minton et al, 2012;Ni & Purda, 2012;Nodeh et al, 2015). However, there result contradict from previous literatures with McNulty et al (2012) and Shirouyehzad, Hosseinzadeh Lotfi, and Dabestani (2014) where higher proportion of non-executive directors are not initiate to have any major effect on corporate risk.…”
Section: Correlation Analysissupporting
confidence: 86%
“…The result is in line with Minton et al (2012), Cheng et al (2016), Ni and Purda (2012) and Nodeh et al (2015) which suggested that more independent directors would enhance consistent and transparent decision making as well as reduce the risk of the firm.…”
Section: Multiple Regressionsupporting
confidence: 83%
See 2 more Smart Citations
“…SMEs performance 2.2.4 Entrepreneurial resilience and risk-taking propensity as mediation roles. Nodeh et al (2015) revealed that a positive association between financial performance and board structure variables was partially mediated by RTP. On the other hand, Khan et al (2022) explored how ER partially mediated the emotional intelligence and SME performance linkage.…”
Section: Encouragingmentioning
confidence: 95%